Knowledge And Perception Regarding Safe-Use of Natural Health Products Among Undergraduates - Yusoff, Yusnaini Md; Din, Wardah Mustafa; Jafry, Nurul Hanis Aminuddin; Rahim, Azlan Abdul; Rusly, Noor Sharizad; Arham, Ahmad Firdhaus; Aziz, Muhammad Firdaus; Nazri, Nurul Syakirah; Hasim, Nur Asmadayana; Yaacob, Mashitoh (Journal of Ecohumanism, 2024)
Awareness of healthy living has driven youth, including undergraduates, to prefer natural health products (NHP). With the rise of online sales for medications, supplements, and cosmetics, understanding NHP safety among undergraduates is crucial. A university elective course included a KYM module on NHP safety. A one-group pre- and post-test study (n=48) assessed the module’s impact using a questionnaire covering demographics, self-assessed knowledge (15 items), and perception (8 items). Frequency analysis and paired sample T-tests evaluated the results. The paired T-test showed significant improvement (p<.05) in students’ knowledge and perception post-course. Knowledge gains were observed in safe use, risks, practices, and regulations. The mean of two perception items shows a modest decrease in comparison to the pre and post-test. This shows that this course improved NHP effectiveness and safety knowledge. In summary, the elective course offered for undergraduates regarding safe use of NHP excellently improved self-assessed knowledge and perception towards NHP. The module embedded in the elective course can be used as a module to also educate other segment of consumers to safeguard them from unnecessary risks to health.